The A CRITICAL ANALYSIS OF HUMAN TRAFFICKING IN INDIA - Arpana Bansal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Human trafficking means the trade of the human in different forms. Human trafficking is a crime and a human right violation. It involves the recruitment, movement and exploitation of a man for profit men, women and children are trafficked in India for various causes. Human trafficking which is for the purposes of sexual exploitation is becoming an increasingly prevalent issue around the world. This paper review the scenario of human trafficking in India. Causes of human trafficking, legal frameworks to counter human trafficking in India are also presented in this paper.